Nonconsensual Distribution of Intimate Images: Exploring the Role of Legal Attitudes in Victimization and Perpetration - Said, Iman (Journal of interpersonal violence, 2023)
In the last 10 years, following widespread outcry among legal scholars and activists, 48 states passed legislation explicitly criminalizing the nonconsensual distribution of intimate images (NCDII) or what is colloquially known as “revenge porn.” This increased authority granted to criminal justice agencies, coupled with greater media attention to NCDII incidents, may have influenced patterns of victimization and perpetration. Using a survey recently distributed to a sample of young adults (N = 713), we find that NCDII perpetration is strongly related to previous victimization, risky online behaviors, and receipt of unsolicited images. Perceptions of police efficacy in addressing NCDII issues is the strongest predictor of attitudes toward both reporting victimization and the belief that perpetrators will experience some punitive consequence. We also conducted an experiment using vignettes with gender varying victim-offender dyads to explore how gender bias influences attitudes toward punishment for NCDII perpetrators as well as perceptions of “revenge porn” in incidents involving same-sex and mixed-sex couples; we find that respondents are less likely to attribute “revenge porn” or to suggest punitive responses when the perpetrator is female regardless of the gender of the victim. Importantly, we find initial evidence of a new typology of NCDII perpetrator that counters existing research on victim–perpetrator gender dyads: women who nonconsensually disseminate unsolicited intimate images sent by men. Collectively, our findings challenge the efficacy of existing criminal statutes, identify new challenges in effectively legislating against NCDII, and contribute to the body of work on gender-based violence, perceptions of police efficacy, and punitive attitudes.